Treatment Decision Making in African American Women Diagnosed with Advanced Breast Cancer - (:unkn) unknown (My University, 2014)
ABSTRACT TREATMENT DECISION MAKING IN AFRICAN AMERICAN WOMEN DIAGNOSED WITH ADVANCED BREAST CANCER by Dauphne Annette Sims When diagnosed with breast cancer African American women have more advanced stage breast disease and encounter disparities throughout the cancer care continuum. The process of making treatment decisions can widen or narrow disparities in health outcomes. The decision making process in African American women may be influenced by several dynamics that influence how treatment decisions are made and have been previously unexplained. Guided by the conceptual framework of Cultural Capital, this grounded theory study explored the treatment decision making process of 12 African American women who were diagnosed with advanced (stags II-IV) breast cancer. The basic social process of Fortitude in Treatment Decision Making emerged from the data. Fortitude described an internal process that participants garnered to make treatment decisions and face the breast cancer journey. Utilizing Fortitude, participants described a treatment decision making process that included getting the diagnosis, communication with their physician, choosing a decisional pathway, and physician trust and/or mistrust that facilitated them in making treatment decisions. This study provides nurses with a more thorough understanding of the decision making process in African American women facing advanced stage breast cancer.
Keywords: African American; Breast Cancer; Cultural Capital; Decision Making; Grounded Theory; Treatment